Chemical and cultural control of armoured bush cricket, Acanthoplus discoidalis (Walker) (Orthoptera: Tettigoniidae: Hetrodinae), in sorghum in Botswana - Scholtz, Clarke H. (University of Pretoria, 2013)
Thesis (PhD (Entomology))--University of Pretoria, 2007.